Advances in Structural and Multidisciplinary Optimization Proceedings of the 12th World Congress of Structural and Multidisciplinary Optimization (WCSMO12) (Springer International Publishing, 2018)
The volume includes papers from the WSCMO conference in Braunschweig 2017 presenting research of all aspects of the optimal design of structures as well as multidisciplinary design optimization where the involved disciplines deal with the analysis of solids, fluids or other field problems. Also presented are practical applications of optimization methods and the corresponding software development in all branches of technology.